Conceiving of and politically responding to NEETs in Europe: a scoping review - Petrescu, Claudia; Voicu, Bogdan; Heinz-Fischer, Christin; Tosun, Jale (Humanities and Social Sciences Communications, 2024)
Young people Not in Employment, Education, or Training (NEET) have become a target population of policymaking in Europe. After one decade of political attention and corresponding policy action, we consider it a good time to take stock of the literature that has dealt with young people who are classified as NEET and the policies adopted in response to the risk of leaving this group of vulnerable individuals behind. To this end, we carry out a systematic review of 83 articles published between 2011 and 2022 in pertinent journals indexed in the Web of Science (WoS). Our scoping review investigates how i) NEETs are defined in the literature, ii) which factors the authors have reported to be relevant for explaining whether a young person becomes NEET, and iii) how policymakers have responded to the existence of this group. We find that there exists no unanimous definition in the literature of young people classified as NEET, even though the European Union has enacted policies that target them. Our review also highlights that individual-level factors as much as contextual variables and policies determine the likelihood of individuals entering into the NEET status and that it matters whether young people live in urban or rural areas. Lastly, the literature has shown that European policymakers have adopted a wide range of policy responses in order to engage young people in employment, training, or education.
Gesehen am 10.06.2024